Enhanced Production of Five-Membered Ring Compounds Using a Biochar-Loaded Fe Catalyst: Catalytic Upgrading of Light Bio-Oil - Lv, S.; Xu, H.; Wu, W.; Yu, Yun; Yang, J.; Gao, A.; Huang, Y.; Tahir, M.H.; Ding, K.; Zhang, S. (2025)
The catalytic upgrading of light bio-oil (LB) is essential for enhancing the overall utilization of crude bio-oil. This study presents the synthesis of a biochar-loaded Fe catalyst (Fen-STC) via a simple one-step pyrolysis method and evaluates its performance in the upgrading of LB. The Fe species were primarily loaded onto the biochar carrier in the form of iron oxides (Fe3O4/Fe2O3), which further etched the biochar carrier, resulting in a substantial alteration of its structure and aromaticity. The optimized Fe1.0-STC exhibited a substantial increase in the specific surface area and a uniform distribution of iron oxides. Notably, this catalyst significantly enhanced the selectivity for producing five-membered ring compounds, such as cyclic ketones and furans, achieving a relative abundance of 70.23%, an increase of 87.74% compared to the control group. Further examination of hydroxyacetone and 1-hydroxy-2-butanone as model compounds elucidated the mechanisms underpinning catalytic upgrading, revealing a synergistic effect that facilitated the transformation of linear short-chain ketones into high-value cyclic compounds through aldol condensation, dehydration, and cyclization reactions. These findings suggest that the Fen-STC catalyst is a promising candidate for enhancing the quality of LB.